Thermal and viscosity characterization of two asphalt emulsions - Kobelnik, Marcelo; Valentin, Leonardo Antônio; Valentin, Clever Aparecido; Lavoie, Fernando Luiz; da Silva, Jefferson Lins; Ribeiro, Clóvis Augusto [UNESP] (Springer Nature, 2022)
Asphalt emulsion is a versatile product that can be used for different waterproofing applications in civil construction and highway constructions. Emulsions also can be used in soil stabilization or applied to the surface of pavement bases and sub-bases. Emulsions with and without the presence of polymers as additives show differences in viscosity, which implies different forms of application. The aim of this paper was the characterization of two asphalt emulsions designated as “fast curing” asphalt emulsions: polymer-free emulsion (RR-C) and polymer emulsion (RR-C-S), with the presence of SBS elastomer (Styrene–Butadiene–Styrene) in its composition. These samples were analyzed by thermogravimetry (TG), derivative thermogravimetry (DTG), differential thermal analysis (DTA) and the viscosity was also determined. In addition, obtaining activation energy by TG/DTG from dehydration and decomposition were carried out under nitrogen purge gas. Thermal characterizations showed that the dehydration of both samples exhibited a high difference in water loss, as well as a different decomposition behavior. The kinetic study of dehydration and decomposition showed that for both samples it has energy value activation keys close to each other.
Keywords: Activation energy; Asphalt emulsion; Thermogravimetry; Viscosity